The Role of Affordable Mortgages in Improving Living Standards and Stimulating Growth : A Survey of Selected Mena Countries - Nothaft, Frank (IMF Working Papers; Working Paper ;, 2002)
This paper argues that making affordable home mortgage loans available to a large cross section of the population will serve both the redistributive and growth-enhancing objectives of poverty reduction policies. The current state of housing and mortgage markets in selected Middle East and North Africa (MENA) countries (Algeria, Egypt, Jordan, Morocco, and Tunisia) is examined. The study evaluates Turkey and Mexico as middle-income comparator countries. Historical experience of the United States is also described. Simulations based on U.S. parameters provide some guide to the effects on economic growth of alleviating housing shortages by improving access to mortgage financing.